A facile nonpolar organic solution process of a nanostructured hematite photoanode with high efficiency and stability for water splitting. Issue 8 (28th October 2015) - Wang, Jian-Jun; Hu, Yelin; Toth, Rita; Fortunato, Giuseppino; Braun, Artur
Abstract : A facile nonpolar organic solution approach has been developed for a high performance hematite photoanode at a low sintering temperature (550 °C). Abstract : We present a facile nonpolar organic solution synthesis and processing method for water splitting photoanodes based on iron oxide with a relatively low sintering temperature (550 °C). The photocurrent of these photoanodes can reach 3.3 mA cm −2 at 1.23 V vs. RHE with high IPCE and stability, which makes them highly attractive candidate photoanodes for hydrogen generation.